Associations between different triglyceride glucose index-related obesity indices and periodontitis: results from NHANES 2009–2014 - Liyuan Yang; Shiyan Fang; Runzhen Zhang; Rong Xia (Lipids in Health and Disease, 2024)
Abstract Background This study aimed to explore the associations between triglyceride glucose (TyG) index-related obesity indices and periodontitis within the American population. Methods This cross-sectional investigation utilized data from the National Health and Nutrition Examination Survey (NHANES) for 2009–2014. The association between the TyG–waist-to-height ratio (TyG-WHtR), TyG–weight-adjusted-waist index (TyG-WWI), TyG–waist circumference (TyG-WC), or TyG–body mass index (TyG-BMI) and periodontitis was investigated utilizing multivariable logistic regression model, subgroup, and dose-response curve analyses. Results This study enrolled 4,808 adult participants. Except for TyG-BMI, which did not exhibit a relationship with periodontitis, TyG-WHtR, [odds ratio (OR) (95% confidence interval (CI))] = 2.83 [1.58–5.10], P = 0.002], TyG-WWI [OR (95% CI) = 7.50 (3.06–18.34), P < 0.001], and TyG-WC [OR (95% CI) = 2.12 (1.23–3.64), P = 0.011] were all associated with periodontitis. Participants in the highest quartile displayed an elevated risk of periodontitis relative to their counterparts in the lowest quartile, as evidenced for TyG-WWI [OR (95% CI) = 1.72 (1.26–2.33), P = 0.001] and TyG-WC [OR (95% CI) = 1.50 (1.13–1.99), P = 0.009] in the full adjustment model. Subgroup analyses suggested more pronounced positive associations between these indices and periodontitis in participants who were < 60 years old, had a BMI ≥ 25, and did not have diabetes. The dose-response curve indicated linear responses in these associations. Conclusions This investigation identified a significant and stable association between TyG-WHtR, TyG-WWI, or TyG-WC and periodontitis, which implies a robust correlation between high insulin resistance and susceptibility to periodontitis in the American population.